Correlation Between Serology Test Result of Leptospira sp. With The Representation of Histopathological Lesions on The Cattle Kidneys - Asih Rahayu; Yos Adi Prakoso; Kurnia Desiandura (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Leptospirosis is an eminent diseases among human and animal health. As a zoonosis disease, the occurrence of leptospirosis is not clearly understood in animal. Furthermore, the lesion caused by Leptospira sp. is not well demonstrated. This study aimed to analyze the correlation between the result of serological test using microscopic agglutination test (MAT) and the representation of histopathological lesion in kidney from the cattle. This study used 28 samples consist of cattle serum and kidney organs. The serum was tested using MAT and kidney was tested using histopathology. The data was reported semi quantitatively and tested using Spearman test. The result showed that there is no correlation between the result of serological test to the representation of histopathological lesion from the kidney of cattle. It is supported by the coefficient correlation (0,05) and probability value p=0,78 (p≥0,05). In conclusion, the result of Leptospira sp. serological test either seropositive or seronegative uncorrelated to the representation of histopathological lesion from the cattle kidney.